Evaluation of the Capacity and Function of Fish Marketing Stations in Ternate Marine Port, North Maluku - Utami, Nanda E. Alif; Taeran, Imran; Karman, Amirul; Irham, Irham; Iksan, Kusdi Hi.; Muksin, Darmiyati (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Ternate Perikanan Nusantara Port (PPN) has functional facilities including the Fish Marketing Point (TPI), which is used as a place to sell fish for some local fish traders. The development of TPI is quite rapid so that it has undergone additions and changes into TPI I, TPI II, and Hygienic TPI. This condition is suspected that TPI will continue to develop in line with the increasing human needs for fishery products. The purpose of this research is to describe fish marketing activities in VAT, and analyze the level of utilization and function of TPI. The method used in the research is descriptive, data collection is done through direct observation and interview with the manager of Ternate VAT. Data analysis consisted of descriptive analysis and utilization level analysis. The result shows that TPI I is functioned as pelagic fish selling place, TPI II is used as demersal fish selling place, while TPI Hygiene is not functioned as fish selling place but as tuna and skipjack temporary storage place before distributed to industry. The utilization rate of TPI I and TPI II have exceeded the optimal level respectively (160.34%, 115.98%), and TPI Hygiene 35.30%.